PENENTUAN ZONA PROSPEK RESERVOIR HIDROKARBON PADA TAHAP EKSPLORASI DENGAN ANALSIS PETROFISIKA FORMASI BATURAJA LAPANGAN “IRFA” BLOK SEKAYU CEKUNGAN SUMATERA SELATAN - Rizky Septianingrum; Hadi Nugroho; Wahju Krisna Hidajat; Herlina Rachman; Yermia Heriadji (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2014)
South Sumatera basin is one of the basin area in Indonesia that has considerable hydrocarbon potential, particularly in the field by IRFA well as the research of the physical properties of a reservoir characteristics including type of lithology, shale volume, porosity, permeability and water saturation value which is fundamental to the activities of oil and gas exploration.The purpose of this research was to determine the physical properties of the reservoir that developed in the areas include shale volume (Vsh), porosity (Ф), permeability (K), water saturation (Sw) zone which in turn can be determined that there is the prospect of hydrocarbon reservoir in the reservoir-3 on the well IRFA-1. The method used is descriptive method is a method that is done from multiple libraries. While the analytical methods used are qualitative analysis and quantitative. Qualitative analysis is to conduct research lithology and correlation of 7 wells located in the study area, while for the quantitative analysis was conducted on the calculation of reservoir petrophysical properties among other shale volume, porosity, permeability and water saturation then be determined net pay identified as areas reservoir will know where is hydrocarbon prospects and the prospects for the determination of hydrocarbon reservoir zones in this study is supported by the chromatograph of analysis done by knowing the value of the total gas C1, C2, C3, iC4, nC4 IRFA-1 well.Based on data analysis and discussion of reservoir-3 well IRFA-1 has a value of shale volume average of 22%, porosity 26%, permeability 371 mD, water saturation of 38%. This calculation is obtained by using a cutoff value for the volume of shale reservoirs <50%, effective porosity >9%, water saturation <60%. The results of the calculation of the average value cromatograph C1 / C2 = 4.14 ppm, C1 / C3 = 7.34 ppm, C1 / C4 = 18.46 ppm, C2 / C3 X 10 = 17.8 ppm. From the results of the data analysis and discussion can be interpreted that the reservoir-3 well IRFA-1 at a depth of 4298.3 to 4353 feet of a reservoir zone with oil prospects.